Transposon-derived small RNAs triggered by miR845 mediate genome dosage response in Arabidopsis. (February 2018) - Borges, Filipe; Parent, Jean-Sébastien; van Ex, Frédéric; Wolff, Philip; Martínez, German; Köhler, Claudia; Martienssen, Robert
Abstract Chromosome dosage has substantial effects on reproductive isolation and speciation in both plants and animals, but the underlying mechanisms are largely obscure1 . Transposable elements in animals can regulate hybridity through maternal small RNA2, whereas small RNAs in plants have been postulated to regulate dosage response via neighboring imprinted genes3, 4 . Here we show that a highly conserved microRNA in plants, miR845, targets the tRNAMet primer-binding site (PBS) of long terminal repeat (LTR) retrotransposons inArabidopsis pollen, and triggers the accumulation of 21–22-nucleotide (nt) small RNAs in a dose-dependent fashion via RNA polymerase IV. We show that these epigenetically activated small interfering RNAs (easiRNAs) mediate hybridization barriers between diploid seed parents and tetraploid pollen parents (the 'triploid block'), and that natural variation for miR845 may account for 'endosperm balance' allowing the formation of triploid seeds. Targeting of the PBS with small RNA is a common mechanism for transposon control in mammals and plants, and provides a uniquely sensitive means to monitor chromosome dosage and imprinting in the developing seed. A conserved microRNA targets LTR retrotransposons inArabidopsis pollen, stimulating epigenetically activated siRNAs in a dose-dependent manner through RNA Pol IV. These miR845b-dependent easiRNAs mediate the interploidy hybridization barrier that leads to seed abortion.